2019
DOI: 10.3892/ol.2019.9997
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complication and postoperative pulmonary function in patients undergoing tumor surgery with thoracic wall resection

Abstract: Postoperative complications of thoracic wall resection include respiratory complications, skin necrosis and infection. The aim of the present study was to examine postoperative complications in patients who required combined thoracic wall resection during the surgical removal of a tumor. The present study included 68 patients; there were 50 patients with lung tumors and 18 patients with musculoskeletal tumors. The clinical factors associated with complications were compared between the two groups. Preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Respiratory complications are an important source of morbidity after chest wall resection, in particular in elderly patients (45) or in case of combined pneumonectomy (46). Thus, careful patient selection and availability of specialized facilities for postoperative care are mandatory to limit postoperative deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory complications are an important source of morbidity after chest wall resection, in particular in elderly patients (45) or in case of combined pneumonectomy (46). Thus, careful patient selection and availability of specialized facilities for postoperative care are mandatory to limit postoperative deaths.…”
Section: Discussionmentioning
confidence: 99%
“…After the first search, 1,343 records were found, and a second selection was made by the title, extracting 102 papers. Of these 102 papers, 16 were finally chosen for review (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Studies evaluating the combination of rigid and semi-rigid prostheses were included only if a subgroup analysis for semirigid materials was done.…”
Section: Resultsmentioning
confidence: 99%
“…30 32,33 In contrast, a recent study of 16 patients by Hayashi et al found a reduction in VC (24.6%, P < 0.01) and an increase in FEV 1 (16.3%, P < 0.01). 34 However, they noted that the decreased VC in 13 of the 16 patients was related to patients having had a pneumonectomy, and patients had a trend toward a restrictive pattern of dysfunction. 34…”
Section: Chest Wall In Respirationmentioning
confidence: 97%
“…34 However, they noted that the decreased VC in 13 of the 16 patients was related to patients having had a pneumonectomy, and patients had a trend toward a restrictive pattern of dysfunction. 34…”
Section: Functions Of the Chest Wallmentioning
confidence: 97%
See 1 more Smart Citation